Структура народжуваності в Україні на початку ХХІ століття - Шевчук, П.Є. (Інститут демографії та соціальних досліджень НАН України, 2010)
В статті розглянуто структурні зміни в моделі народжуваності в Україні в 2000–2008 рр. за віком матері, черговістю дітонародження. Показано подібність процесів трансформації народжуваності в міській та сільській місцевості. Виявлені особливості впливу зрушень у сучасній віковій структурі жінок, в тому числі й за типом поселення. Подано особливості змін у структурі дітонародження за національністю матері. В статье рассмотрены структурные изменения в модели рождаемости в Украине в 2000–2008 гг. по возрасту матери, очередности деторождения. Показано подобие процессов трансформации рождаемости в городской и сельской местности. Выявлены особенности влияния сдвигов в современной возрастной структуре женщин, в том числе и по типу поселения. Представлены некоторые особенности изменений в структуре деторождения по национальности матери. At the beginning of XXI century Ukraine is reached the lowest fertility in its whole observation history. A rapid increasing of TFR last years can be explained not recuperation only. Thus the generations who enter into childbearing age in last years could be the first that starts adopt a new fertility model – with postponed first births. In the same time elder cohorts begin to realise the second (and the next) order birth, which delayed in last XX decade. This trend led to growing up the parity-specific (and total) fertility rates. The analysis shows that essential features of modern Ukrainian fertility model transformations pursue the European one with time lag. While rural fertility in Ukraine is more traditional it follows the urban one. At the same time age structure was more favourable for urban population. But in the near future structural proportions in childbearing ages would be changed for benefit rural women in most childbearing ones. After substantial increasing child assistance in 2005 fertility rates growth more intensively in rural area. This reveals evident income inequality between urban and rural populations. But in any case the Ukrainian value TFR already overcome the magnitude of TFR in many European countries. Also there is substantial increasing of share of born by Muslim women in Ukraine in recent years. The lack of initial data don’t allow make out in-depth analysis in this field. In conclusion the analysis shows an intense influence of various structural factors on fertility dynamics in Ukraine: the age structure (such as age distribution of women and age fertility profile), parity-specific fertility distortions and shifts in childbearing by nationality of mother.